Diagnosing Borreliosis - Cutler, Sally J; Rudenko, Nataliia; Golovchenko, Maryna; Cramaro, Wibke J; Kirpach, Josiane; Savic, Sara; Christova, Iva; Amaro, Ana (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2017)
Borrelia species fall into two groups, the Borrelia burgdorferi sensu lato (Bbsl) complex, the cause of Lyme borreliosis (also known as Lyme disease), and the relapsing fever group. Both groups exhibit inter- and intraspecies diversity and thus have variations in both clinical presentation and diagnostic approaches. A further layer of complexity is derived from the fact that ticks may carry multiple infectious agents and are able to transmit them to the host during blood feeding, with potential overlapping clinical manifestations. Besides this, pathogens like Borrelia have developed strategies to evade the host immune system, which allows them to persist within the host, including humans. Diagnostics can be applied at different times during the clinical course and utilize sample types, each with their own advantages and limitations. These differing methods should always be considered in conjunction with potential exposure and compatible clinical features. Throughout this review, we aim to explore different approaches providing the reader with an overview of methods appropriate for various situations. This review will cover human pathogenic members of Bbsl and relapsing fever borreliae, including newly recognized Borrelia miyamotoi spirochetes.
Keywords: členovci - vektory; návratná horečka; Lyme Disease; lymeská nemoc; Ticks; Animals; Humans; Lyme disease; Borrelia; lidé; klíšťata; Arthropod Vectors; zvířata; Relapsing Fever; diagnosis; Borrelia species; relapsing fever